Improvement Plan for Teaching Law in Colombia - Ramírez Guerrero, Carlos Francisco (DIXI, 2016)
Purpose: there is a belief in Colombia that any lawyer can be a Law teacher in a school legally incorporated for such purpose. At present, teachers in the schools of Law are not well prepared in education to train lawyers.Description: what is essential, in this case, is to implement a system where Law teachers take pedagogy lessons so that they arrive to the classroom with the best intention of transmitting knowledge, away from old forms of teaching, and that future lawyers are duly prepared to face legal proceedings and issues in real life.Point of view: in Colombia, following the tradition that teachers teach the way they were taught is asymptomatic fact. Tht is exactly what this study intends to change. Teaching Law requires much more than the mere legal knowledge of the person who intends to give lectures at a school of Law.Conclusions: it is necessary to change the law teaching structure; it is important that teacher commits to change and putting it into practice.
Keywords: lawyers; Law; teacher; teaching; pedagogy; knowledge